1992
DOI: 10.3109/03093649209164320
|View full text |Cite
|
Sign up to set email alerts
|

A new model of plastic ankle foot orthosis (FAFO (II)) against spastic foot and genu recurvatum

Abstract: A plastic ankle foot orthosis (AFO) was developed, referred to as functional ankle foot orthosis Type 2 (FAFO (11)), which can deal with genu recurvatum and the severe spastic foot in walking. Clinical trials were successful for all varus and drop feet, and for most cases of genu recurvatum. Electromyogram studies showed that the FAFO (11) reduced the spasticity of gastrocnemius and hamstring muscles and activated the quadricep muscles. Gait analysis revealed a reduction of the knee angles in the stance phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The management of spastic drop-foot is the prescription of an AFO, which is designed to provide ankle stability during stance and adequate toe clearance during swing and to promote heel strike 15,16. In previous studies, cases with and without AFOs have been compared,18,19 while in some studies, different types of AFOs have been analyzed 20,21. Most of the studies performed thus far have focused on the kinematic study of the ankles22,23 or have evaluated the effectiveness of AFOs using a systematic approach 24.…”
Section: Introductionmentioning
confidence: 99%
“…The management of spastic drop-foot is the prescription of an AFO, which is designed to provide ankle stability during stance and adequate toe clearance during swing and to promote heel strike 15,16. In previous studies, cases with and without AFOs have been compared,18,19 while in some studies, different types of AFOs have been analyzed 20,21. Most of the studies performed thus far have focused on the kinematic study of the ankles22,23 or have evaluated the effectiveness of AFOs using a systematic approach 24.…”
Section: Introductionmentioning
confidence: 99%
“…Ohsawa S et al [21] The effect of FAFO (Foot AFO) was tested in this research. Of 39 patients 23 had genu-recurvatum mostly due to CVA.…”
Section: Tablementioning
confidence: 99%
“…In the study done by Ohsawa et al, it was shown that walking speed of stroke subjects improved following the use of AFO. Moreover, Genu-recurvatum was modified in 21 of the subjects [21]. The effects of using AFO with 90 stop, with heel high compensation and with ¾ length foot plate for the patients with post stroke hemiplegia was investigated by Fatone S et al Based on the results of their study, use of AFO did not influence the walking speed [17].…”
Section: The Effects Of Using Afo On Knee Joint Hyperextensionmentioning
confidence: 99%
“…The use of NAAFOs are reported to increase gait velocity, decrease double stance duration, improve the symmetry ratio of stance duration and of deceleration force, increase step length of the paretic limb, decrease body sway in stance, normalize heel strike, improve control of inversion of the foot, and improve activities of the hamstrings and calf muscles. 2–9 The use of AAFOs has shown improvement of gait velocity, cadence, stride length, single stance duration of the paretic limb, and dorsiflexion angle of the paretic ankle joint during stance. 10–13 Comparing the two kinds of AFOs, Weis et al reported that NNAFOs impeded the natural movement of the ankle joint in stance and shortened the step length, resulting in slower velocity.…”
Section: Introductionmentioning
confidence: 99%